MYTHO-LOGIC IN NON-CLASSICAL HUMANITIES REFLECTIONS ON MYTH: METHODOLOGICAL ASPECT - Олексін, Данило (Ukrainian Cultural Studies, 2023)
Over the past century, a lot of conceptual reflections on myth have been accumulated; however, there has been no attempt to systematically objectify and catalog such investigations. The relevance of research can be divided into two loci: the general and the particular. The general relevance is based on the high level of entwinement of myth and its motifs within contemporary culture; the particular aspect is due to the need to objectify the 20th-century theories of myth and to define their general method (1), and to enrich cultural discourse with new works in the field of myth philosophy (2). The goal of the research is to overview the process of the emergence of myth science within the context of the late 19th-century re-mythologization as an ontological argument for cultural mythological research; to define mytho-logic as a synthetic method of non-classical interpretation of mythological material. Methods: comparative (in the analysis of 20th-century approaches to studying myth and defining the non-classical concept of myth). Objectives: to explore the components of myth science; to define the concept of re-mythologization; to argue for mytho-logic as a non-classical model for interpreting myth. Results: the components of myth science that represent a sum of non-classical approaches to studying "sacred narrative" (ritual, functional, sociological, psychoanalytic, structural, transcendental, and numinous approaches) have been investigated; the concept of re-mythologization as the actualization of myth as the object of scientific, philosophical, and artistic interest has been defined; the mytho-logic as a non-classical model of myth interpretation through its structure and logic has been justified. Conclusions: the study of myth has risen on the cognitive waves of the deep ocean of modern humanities to the heights of a problem-filled space of culture studies. Through this actualization, it has gained an interdisciplinary character and has become a dozens-of-definition concept that roams from realm to realm – just like the concept of "culture" itself. Principles of the mytho-logic can and should be expanded, as myth can be studied through any presented in myth science paths. This paradigm is not self-contained and provides variability and aspectuality in considering myth as a cultural universality, and thus is convenient and justified for use in the context of non-classical philosophy and contemporary cultural studies.